Management of Regulatory Influences on Corporate Strategy and Structure - Frankenberger, Sebastian (Deutscher Universitätsverlag : Imprint: Deutscher Universitätsverlag, 2006)
In many industries, e.g. telecommunications, transportation, energy, chemicals, food and beverages, firm performance is heavily influenced by regulation. Despite this fact, strategic management research has traditionally focused on market strategies and related issues. Questions of how to manage regulatory involvement have been left to separate research streams on corporate political activity and a broader understanding of the complex inter-dependencies and mutual influences between corporate and external actors remains lacking. Sebastian Frankenberger examines how to integrate external actors, regulatory actors in particular, into the strategy formation process. Based on a longitudinal, retrospective case study on the German energy utility E.ON., he analyses how regulatory actors influence corporate strategies and structures and how corporations may proactively manage regulatory involvement. He presents a theoretical framework that integrates market and political strategies and shows how corporations may influence institutional processes that impact their scope of operations. He also suggests options how management can navigate their business within institutional boundaries and how market and political strategies may be coordinated.